2019
DOI: 10.1016/j.ajic.2018.11.021
|View full text |Cite
|
Sign up to set email alerts
|

User acceptance of reusable respirators in health care

Abstract: Background: Inclusion of reusable respirators, such as elastomeric half-face respirators (EHFRs) and powered air-purifying respirators (PAPRs), in hospital respiratory protection inventories may represent 1 solution to the problem of N95 respirator shortages experienced during pandemics. User acceptance of these devices is 1 potential barrier to implementing such a strategy in respiratory protection programs. Methods: To assess user attitudes toward various respirators, health care workers enrolled in respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(102 citation statements)
references
References 14 publications
3
99
0
Order By: Relevance
“…For example, previous research found that elastomeric respirator users, who rated the respirators less favorably with respect to comfort, but higher in perceived level of protection, still preferred to use them in certain higher risk scenarios, such as during pandemic influenza. 9 Acceptance of less convenient but more protective safeguards may be more pronounced among HCWs while providing care to COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, previous research found that elastomeric respirator users, who rated the respirators less favorably with respect to comfort, but higher in perceived level of protection, still preferred to use them in certain higher risk scenarios, such as during pandemic influenza. 9 Acceptance of less convenient but more protective safeguards may be more pronounced among HCWs while providing care to COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…HCWs enrolled in a medical system's respiratory protection program were queried both during a focus group interview of 11 hospital staff members and a larger medical system-wide electronic survey of 1,152 HCWs regarding their perceptions and beliefs about the impact of respirators on their ability to provide patient care. 8,9…”
mentioning
confidence: 99%
“…These reusable respirators are used in construction and manufacturing, but not widely used in health care 4 because of uncertainty about disinfection methods and upfront costs. 5 The goal of this demonstration study was to test the feasibility of rapidly training and fit testing health care workers to EHMRs. which health care personnel, who were randomized to EHMR (80%) or N95 (20%) groups, were rapidly fit tested and trained.…”
Section: Training and Fit Testing Of Health Care Personnel For Reusabmentioning
confidence: 99%
“…We divided our population using the National Center for Health Statistics urban-rural classification scheme into large metropolitan (≥1 million), medium and small metropolitan (50 000-999 999), and rural (<50 000) counties per the 2013 US Census classification. 5 Because data were publicly available and deidentified, ethics committee approval was not required.…”
Section: Rural-urban Differences In Cardiovascular Mortality In the Umentioning
confidence: 99%
“…Additionally, PAPRs have been found favorable to HCWs in 6 high risk scenarios. This is because the devices are reusable and give the user a better sense of protection [14]. A study performed by Khoo…”
Section: N95 Vs Papr -Emergency Readinessmentioning
confidence: 99%